2019
DOI: 10.1155/2019/5769514
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms -455G/A and -148C/T and Fibrinogen Plasmatic Level as Risk Markers of Coronary Disease and Major Adverse Cardiovascular Events

Abstract: Some polymorphisms in genes codifying for fibrinogen have been correlated with plasma levels of this protein, and several studies reported their associations with acute cardiovascular events. In the present study, 118 subjects with unstable and stable coronary diseases were enrolled to determinate the associations among fibrinogen gene polymorphisms, plasma fibrinogen levels, and major cardiovascular adverse events in a sample of southwestern Mexico. The groups, including 81 control subjects, were matched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…gen plays a major role in platelet aggregation via enzymatic conversion to fibrin and is also the main determinant of plasma viscosity and erythrocyte aggregation [13]. Several studies and meta-analyses have investigated the association between the fibrinogen level and cardiovascular diseases [14,15]. Fibrinogen was found to be an independent risk factor for cardiovascular disease in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…gen plays a major role in platelet aggregation via enzymatic conversion to fibrin and is also the main determinant of plasma viscosity and erythrocyte aggregation [13]. Several studies and meta-analyses have investigated the association between the fibrinogen level and cardiovascular diseases [14,15]. Fibrinogen was found to be an independent risk factor for cardiovascular disease in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the allelic loads of -455 G/A and -148 C/T were associated with plasma fibrinogen concentrations >450 mg/dL ( p < 0.003 and p = 0.03) and with a risk of CAD ( p = 0.016 and p < 0.006). Moreover, the follow-up of posterior events after an acute coronary event showed that the genetic load of the -148 C/T allele was associated with major adverse cardiovascular events (RR = 1.8; 95% CI: 1.01–3.35, p = 0.04) [ 86 ]. A meta-analysis of 26 clinical trials, by Gu et al, also assessed the association between the -455 G/A polymorphism and the risk of ischemic stroke.…”
Section: Fibrinogen Molecular Modifications and Cardiovascular Riskmentioning
confidence: 99%
“…Cardiovascular disease is a frequently occurring disease that seriously endangers human health. [19][20][21] Many cardiovascular diseases, such as hypertension, valvular disease, myocardial infarction, and congenital heart disease, can lead to cardiac hypertrophy and cause heart failure or even sudden death. [22][23][24][25] Therefore, myocardial hypertrophy has become one of the independent risk factors for cardiovascular disease morbidity and mortality around the world, and its pathogenesis and prevention and treatment have always been the focus of research in the field of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%